Documentos de Mamelucos no Brasil Colonial: edição e descrição dos aspectos gráficos - Souza, Márcia Silva de (2022)
This work presents twenty-five edited manuscripts from the 17th and 18th centuries, belonging to Mamluks that had access to writing during the colonial period. They are rare documents, as they are written by a population of which only few had access to education. That gives them great importance for the study of the history of Brazilian Portuguese and the diffusion of writing. The research followed the proposal of the Project for the History of Brazilian Portuguese (PHPB), meeting the three research proposals: i. the semi-diplomatic edition, according to the PHPB transcription criteria, offering a philologically reliable edition to studies on the history of Brazilian Portuguese (BP); ii. the socio-historical contextualization of the manuscripts, and iii. linguistic studies, in this research, the description of graphophonics. Following the proposal of Barbosa (1999), Marquilhas (2000), Oliveira (2006) and Santiago (2012;2019), some criteria to disability identification are presented, such as: supragraphic and paleographic; graphic segmentation; aspects of writing acquisition, representation of nasality, etc. Some editions of the documents, in semi-diplomatic and modern versions, were made available to contribute to the study of linguistic and socio-historical aspects of the diffusion of writing, among others.